A Case Report of Pin Site Osteomyelitis after 17 Years of External Fixator Application to Distal Radius Fracture - Tan, Tuan Hao; Tang, Camelia Qian Ying; Sreedharan, Sechachalam (Journal of Hand and Microsurgery, 2023)
This case report presents an uncommon long-term complication of external fixator application to distal radius fracture. Despite an initial uneventful fracture healing, the patient presented with Brodie's abscess with Staphylococcus aureus osteomyelitis at the previous pin site 17 years later. A diagnosis of late-onset osteomyelitis, as a manifestation of quiescence chronic osteomyelitis, was made.
Keywords: distal radius fracture; complications; osteomyelitis; negative-pressure wound therapy; skin graft